The effect of gut microbiota dysbiosis on patients with preeclampsia - Zhao, Yefang; Wang, Bingjie; Zhao, Xiaoling; Cui, Dan; Hou, Shaoke; Zhang, Hongzhen (Frontiers in Cellular and Infection Microbiology, 2023)
Purpose To compare the difference of gut microbiota between preeclampsia (PE) and healthy normal pregnant women, providing new therapeutic strategy for preeclampsia. Methods Forty-one PE patients and 45 age- and pre-pregnancy body mass index- matched healthy controls were enrolled from Nov 2021 to May 2022 in this retrospective case-control study. Fecal microbiota was detected by 16S rRNA gene sequencing, followed by bioinformatics analysis including microbial α diversity, microbial β diversity, and linear discriminant analysis effect size (LEfSe) analysis. Serum inflammatory factors were also detected and compared between the two groups. Results There were significant differences in Bacteroidetes (2.68% in PE patients vs 11.04% in healthy controls, P < 0.001), Proteobacteria (4.04% in PE patients vs 1.22% in healthy controls, P = 0.041), and Fusobacteria (1.07% in PE patients vs 0.01% in healthy controls, P = 0.042) between the two groups at the phylum level. Microbial α diversity was lower in PE patients than that in healthy controls. In addition, there was significant difference in microbial β diversity between the two groups. LEfSe analysis showed that there are 24 different taxa between the two groups. The levels of proinflammatory factors including serum tumor necrosis factor-α and Interleukin-6 were statistically significant higher in PE patients than those in healthy controls (both P < 0.001), while there were no significant differences in the levels of serum anti-inflammatory factors including Interleukin-4 and Interleukin-10 between the two groups (P = 0.234 and P = 0.096, respectively). Conclusion PE patients demonstrated gut microbiota disturbances and increasing serum proinflammatory factors, leading to a better understanding of the relationship between the gut microbiota dysbiosis and PE.